A comparative assessment of 16S ribosomal RNA and Cytochrome C Oxidase Subunit I (COI) primers for amphibian DNA Barcoding - Ramli, Farah Farhana; Kaviarasu, Munian; Othman, Nursyuhada; Nur Hartini Sariyati, Nur Hartini Sariyati; Abdullah-Fauzi, Nurfatiha Akmal Fawwazah; Norhakim, Mohd Lokman Ilham; Abdul Latiff, Muhammad Abu Bakar (2023)
Amphibians, a diverse and ecologically important group, are facing global declines due to various factors, including habitat loss and climate change. Accurate species identification is crucial for effective conservation efforts, and DNA barcoding has emerged as a powerful tool in this regard. This study compares the efficacy of two DNA barcoding primer sets, targeting the 16S ribosomal RNA gene and the Cytochrome Oxidase I (COI) gene, for identifying 20 amphibian species. While both primer sets successfully amplified sequences, the 16S rRNA gene region identified all 20 samples, whereas the COI region identified 14. The amplified sequences, approximately 550 base pairs for 16S rRNA and 658 base pairs for COI facilitated precise taxonomic placement within amphibian families using Neighbor-Joining phylogenetic trees. These findings enhance DNA barcoding methodology and aid in understanding amphibian diversity, crucial for effective conservation strategies amidst global declines drives by habitat loss, diseases, and climate change